Electromechanical properties of paper-derived potassium sodium niobate piezoelectric ceramics - Wahl, Larissa; Maier, Juliana; Schmiedeke, Samuel; The-An Pham,; Fey, Tobias; Webber, Kyle Grant; Travitzky, Nahum; Khansur, Neamul Hayet (Journal of the American Ceramic Society, 2022)
The small-signal dielectric and piezoelectric coefficients of paper-derived sodium potassium niobate, K0.5Na0.5NbO3 (KNN), were compared with those of conventionally prepared samples. Results show similar functional properties of paper-derived KNN without significantly decreasing the small-signal piezoelectric coefficient. The structure and microstructure analysis of conventional KNN and paper-derived KNN did not reveal any significant difference in the crystal structure and grain size. However, the temperature-dependent inter-ferroelectric phase transition temperature estimated from the temperature-dependent dielectric permittivity data revealed a decrease of approximately 18°C for the paper-derived KNN and is possibly associated with the structural and microstructural defects. This work indicates that optimizing suspension chemistry and sintering conditions will be critical to enhance the functional response of paper-derived KNN further. Moreover, paper-derived ceramic processing, a novel and cost-effective additive manufacturing technology, can be potentially used to fabricate other electroceramics with a wide range of porosities and sizes as well as complex geometries and multilayer structures.
CRIS-Team Scopus Importer:2022-08-05
Keywords: KNN; lead-free ferroelectrics; paper-derived ceramics; piezoelectrics

Fabrication of Reaction-Bonded Boron Carbide-Based Composites by Binder Jetting 3D Printing - Wahl, Larissa; Schmiedeke, Samuel; Knorr, Moritz; Schneider, Ines; Travitzky, Nahum (Ceramics, 2022)
In this work, the binder jetting 3D printing of boron carbide was combined with a subsequent liquid silicon infiltration procedure to produce reaction-bonded boron carbide (RBBC)-based structures. After printing, the samples were isostatically pressed to obtain more homogeneous and denser microstructures while maintaining their complex shapes. The RBBC bodies were successfully fabricated, and the influence of the binder content on the amount of residual silicon was studied. By increasing the binder content from 10 to 22.5 vol.%, the Si content decreased from similar to 28 to similar to 12 vol.%. The mechanical properties dependent on the Si content were additionally investigated. The measured average values for the bending strength (similar to 355 MPa), Young's modulus (similar to 348 GPa), and hardness (similar to 20 GPa) are comparable to those reported in the literature for RBBC-based materials.
CRIS-Team WoS Importer:2023-01-13

Preceramic paper-derived Ti3Al(Si)C2-based composites obtained by spark plasma sintering - Krotkevich, D. G.; Kashkarov, E. B.; Syrtanov, M. S.; Murashkina, T. L.; Lider, A. M.; Schmiedeke, Samuel; Travitzky, Nahum (Ceramics International, 2021)
The paper describes the structure and properties of preceramic paper-derived Ti3Al(Si)C2-based composites fabricated by spark plasma sintering. The effect of sintering temperature and pressure on microstructure and mechanical properties of the composites was studied. The microstructure and phase composition were analyzed by scanning electron microscopy (SEM) and X-ray diffraction (XRD), respectively. It was found that at 1150 °C the sintering of materials with the MAX-phase content above 84 vol% leads to nearly dense composites. The partial decomposition of the Ti3Al(Si)C2 phase becomes stronger with the temperature increase from 1150 to 1350 °C. In this case, composite materials with more than 20 vol% of TiC were obtained. The paper-derived Ti3Al(Si)C2-based composites with the flexural strength > 900 MPa and fracture toughness of >5 MPa m1/2 were sintered at 1150 °C. The high values of flexural strength were attributed to fine microstructure and strengthening effect by secondary TiC and Al2O3 phases. The flexural strength and fracture toughness decrease with increase of the sintering temperature that is caused by phase composition and porosity of the composites. The hardness of composites increases from 9.7 GPa (at 1150 °C) to 11.2 GPa (at 1350 °C) due to higher content of TiC and Al2O3 phases.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Composites; MAX-Phases; Mechanical properties; Microstructure; Preceramic paper; Spark plasma sintering

Process development for laser powder bed fusion of pure copper - Stoll, Thomas; Trautnitz, Pascal; Schmiedeke, Samuel; Franke, Jörg; Travitzky, Nahum (Proceedings of SPIE, 2020)
This paper describes the development of suitable process parameters to ensure a reproducible, defect-free production of pure copper specimen via Laser Powder Bed Fusion (LPBF) also called Selective Laser Melting (SLM). Therefore, a set of experiments was developed and evaluated in a Design of Experiment (DoE) which finally provide an indication about ideal process parameters for melting pure copper powder at a wavelength of 1064 nm. For the experiments Cu-ETP with a copper purity of more than 99.90 % was processed with a laser power of up to 500 W resulting in a maximum density of 99.82 % and an electrical conductivity of 56.88 MS/m. Besides the development of optimal parameter combinations of laser power, laser speed and hatching distance, focusing the laser beam to a spot diameter of about 35 μm with a fused silica f-theta lens and thus high laser intensities of about 416 kW/mm2 resulted in best materials properties.<br
Keywords: Kupfer; Laser; LPBF

Robocasting of reaction bonded silicon carbide/silicon carbide platelet composites - Wahl, Larissa; Weichelt, Michelle; Goik, Philip; Schmiedeke, Samuel; Travitzky, Nahum (Ceramics International, 2021)
Pastes with a varying amount of uncoated SiC platelets (SiCplatelets) for the fabrication of reaction bonded silicon carbide (RBSC) were developed and the effect of the anisotropic particles on the microstructure and mechanical properties of the fabricated RBSC/SiCplatelets composites was studied. During printing the platelets align in printing direction due to shear forces. This texturization was confirmed by image analysis and EBSD measurement.
CRIS-Team WoS Importer:2021-04-02

Sintering simulations for ceramic multilayer laminates with paper-derived ceramics: From sintering dilatometry to anisotropic sintering simulation - Manière, Charles; Lecourt, Jérome; Dermeik, Benjamin; Schmiedeke, Samuel; Travitzky, Nahum (Journal of the European Ceramic Society, 2024)
Alumina-based multilayer laminates with layers of varied porosities and ceramic fiber reinforcements, which can be achieved by including paper-derived ceramic layers, are interesting candidates for chemically stable and thermal shock resistant materials. In order to investigate the complex sintering behavior of these laminates, the sintering of each alumina layer contained within a laminate, each one with its individual sintering anisotropy and sintering shrinkage, has to be considered separately. For this purpose, sintering curves are determined by dilatometry measurements, serving a consecutive examination by an analytical model. Modeling parameters specific to each layer, are applied in finite-element-type sintering simulations for symmetrical multilayer laminates. Differences in the sintering shrinkages may cause internal stresses at layer interfaces and, in turn, may influence the thermal and mechanical properties of multilayer laminates after sintering. Accordingly, the prediction of developing internal stresses within alumina-based multilayer laminates by the presented sintering simulations is a key aspect of this study.
CRIS-Team Scopus Importer:2024-04-05
Keywords: Anisotropy; Ceramics; Finite Element Method; Laminates; Simulation; Sintering